Normative bladder diary measurements in pregnant women. (March 2017) - Bulchandani, Supriya; Coats, Alfred C.; Gallos, Ioannis D.; Toozs-Hobson, Philip; Parsons, Matthew
Abstract: Objective: Studies have demonstrated a strong positive correlation between bladder capacity and total volume voided in asymptomatic non-pregnant women. Therefore, to adequately characterise the normative data, it was important to compare bladder capacity vs. 24-h volume (V24 ) relationships in our pregnant study population. Our objectives were to (1) collect normative bladder diary measurements from asymptomatic primigravid women, (2) investigate the relationship between these measurements and gestation of pregnancy, and (4) compare these normative measurements from pregnant women with those from asymptomatic non-pregnant women. We focused on measures of "bladder capacity" [average ("Vavg ") and maximum volume per void ("Vmax ")], ("V24 "), and voiding frequency ("F24 "). Study design: Three-day bladder diaries were collected from 41 primigravid women, one three-day diary per trimester. We compared our pregnant data with non-pregnant data previously collected by Amundsen et al. using identical methods. Relationship between variables analysed using the Kruskal-Wallace and Mann-Whitney tests. Results: We found no significant differences across trimesters among bladder diary measurements (p-values: F24  = 0.711; Vmax  = 0.912; Vavg  = 0.894, and V24  = 0.675). A comparison between pregnant and non-pregnant data showed no significant difference between F24, but a significantly lower V24, Vavg and Vmax in pregnant women. Regression analysis showed no significant differences between the pregnant and non-pregnant, V24 vs. bladder capacity relationships. Conclusions: Pregnancy results in smaller bladder capacities and lower V24, with a normal relationship between V24 and bladder capacity, maintaining normal voiding frequency. We used our data to construct a nomogram to help clinicians compare the relative contributions of increased V24 and reduced bladder capacity to increased F24 .